The Impact of COVID-19 Regional Cash Subsidies on the Sales of Local Businesses in South Korea - Meeroo Kim; Yoon Hae Oh (KDI Journal of Economic Policy, 2021)
This paper examines the impact of the regional cash subsidies which were granted in some districts in addition to the national universal stimulus payment in South Korea related to the COVID-19 pandemic. We evaluate the effects of the cash distribution per resident on aggregate credit and debit card sales and sales by industry using the difference-in-difference method. The increment in card spending due to the cash subsidy is about 1.58%p in total, and this effect is concentrated within a single month. The consumption stimulating effect is prominent among (semi)-durable goods that do not require close interactions between customers and sellers. In contrast, the effect is relatively small in the high-contact face-to-face service sectors and restaurants, areas the COVID-19 pandemic hit directly. On the other hand, some service sectors where customers could wear face masks, such as education and fitness, experienced a substantial sales boost due to the cash subsidy.
Keywords: D12; E21; H12; 330; COVID-19; Stimulus Payment; Cash